[Saddle Road Near Port of Spain, Trinidad] - (:unkn) unknown (My University, 2009)
A photograph of the Saddle Road, North Port of Spain, Trinidad in its early days. The road appears to be unpaved and winding. Trees flank the road at left and right. In the foreground, at left of Saddle Road, appears to be four tall, skinny, Bois canot trees. This is a medium sized tree and only one of them has leaves. At mid-ground there is a guard fence which suggests there is a bridge. In the background are numerous trees covering the hillside.
Colour: Black and White; Style: Landscape; Other: Bordered, Divided
Keywords: Trinidad and Tobago; Postcards; Mountain roads--Trinidad and Tobago; Roads--Trinidad and Tobago; Cities and towns--Trinidad and Tobago--Maraval; Roads--Guard fences; [1910]; Scenic byways--Trinidad and Tobago; Forests and forestry--Trinidad and Tobago; Bridges--Trinidad and Tobago; Saddle Road (Trinidad and Tobago)